Early chilhood education in Sweden : the market curriculum 200-2013? - O’Dowd, Mina (Revista Española de Educación Comparada, 2013)
Early childhood education in Sweden has long had an international reputation for being a systemic and integrated approach to children’s needs, a family model of preschool centers and an interest in the holistic development and well-being of children. However, traces of this reputable past are hard to discern today as the neo-liberal agenda for education that is infl uencing education around the world has impacted Sweden. The changes in Sweden, however, have successively occurred since the 1980s, due to the failure of the Swedish economy to provide the necessary surplus to support the extensive social and welfare reforms that previously gave Sweden its international reputation. The effects of the neo-liberal agenda along with the reforms implemented by the Social Democratic government and the Conservative government have had and continue to have an impact on early childhood education in Sweden. As more and more governments are faced with economic problems, the case of Sweden and the measures taken by both the Social Democrats and the Conservative parties over the last few decades make a study of the Swedish reforms of early childhood education relevant and interesting for other countries. In this article early childhood education in Sweden will be presented and discussed from a historical and a conceptual perspective, focusing on its objectives and features and explaining the shifts make by political parties vis-à-vis early childhood education in Sweden. La Educación Infantil en Suecia ha tenido una gran reputación internacional, por tratarse de una aproximación sistémica e integrada a las necesidades de los niños, un modelo familiar de centros prescolares y por su interés en el desarrollo holístico e integral de los niños. Los cambios recientes acaecidos en la educación en Europa y en otros lugares, junto con las reformas emprendidas por el gobierno conservador que ha estado en el poder desde 2006 en Suecia han tenido y continúan teniendo impacto en la educación de la primera infancia. En este artículo se presenta y se discute la educación infantil en Suecia desde una perspectiva histórica y conceptual y se debaten las implicaciones que dichas perspectivas tienen en la educación infantil de este país en la actualidad.